Prenatal stress, immunity and neonatal health in farm animal species*. (6th August 2013) - Merlot, E.; Quesnel, H.; Prunier, A.
Abstract : The high pre-weaning mortality in farm animal species and poor welfare conditions of reproductive females question modern industrial farming acceptability. A growing body of literature has been produced recently, investigating the impact of maternal stress during gestation on maternal and offspring physiology and behavior in farm animals. Until now, the possible impact of prenatal stress on neonatal health, growth and survival could not be consistently demonstrated, probably because experimental studies use small numbers of animals and thus do not allow accurate estimations. However, the data from literature synthesized in the present review show that in ungulates, maternal stress can sometimes alter important maternal parameters of neonatal survival such as colostrum production (ruminants) and maternal care to the newborn (pigs). Furthermore, maternal stress during gestation can affect maternal immune system and impair her health, which can have an impact on the transfer of pathogens from the mother to her fetus or neonate. Finally, prenatal stress can decrease the ability of the neonate to absorb colostral immunoglobulins, and alter its inflammatory response and lymphocyte functions during the first few weeks of life. Cortisol and reproductive hormones in the case of colostrogenesis are pointed out as possible hormonal mediators. Field data and epidemiological studies are needed to quantify the role of maternal welfare problems in neonatal health and survival.